ANALISA KEBUTUHAN DAYA MOTOR LISTRIK PADA MESIN SARI NANAS - Fatra, Fatra; Padilah, Rifky; Saputra, M. Aji; Haritsah Amrullah, Muhammad; Pristiansyah, Pristiansyah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
The pineapple juice extractor machine is used for the process of pressing pineapples to produce juice while separating the pulp. The currently available machines generally use electric motors with a power of 0.35 HP. However, with that motor power, the existing machines are not able to press pineapples optimally, as the electric motor tends to lose power during operation. Therefore, this research focuses on calculating the appropriate motor power to be used in a pineapple juice extractor machine with a capacity of 5 kg/hour. The method applied involves calculating several parameters, including load, capacity, torque, and motor power. This is intended to ensure that the motor used is truly capable of accommodating the desired machine capacity. Based on the calculations performed, the most suitable electric motor for a pineapple juice extractor machine with a 5 kg/hour capacity is one witch a power rating of 0.5 HP.